Individual Surgical Treatment of Stage IV Müller-Weiss Disease According to CT/MRI Examination: A Retrospective Study of 12 Cases - Liu, Wenzhou; Chen, Yanbo; Zeng, Gang; Yang, Tao; Ma, Mengjun; Song, Weidong (Frontiers in Surgery, 2022)
Background This study reported the individual surgical treatment of 12 cases with stage IV Müller-Weiss disease (MWD) according to computed tomography (CT)/magnetic resonance imaging (MRI) examination. Methods Twelve cases diagnosed with stage IV MWD in our hospital from 2015 to 2019 were included in the retrospective study. Relevant clinical outcomes were evaluated preoperatively and postoperatively. Results The follow-up results showed satisfactory outcomes in all cases. All the cases were presented with tenderness and chronic pain on the midfoot dorsum, and 3 cases were also presented with tenderness and pain on the lateral side of the midfoot, in which calcaneal cuboid arthritis were revealed by CT/MRI. AOFAS scores elevated from 62.5 ± 6.8 (range: 53-74) preoperatively to 95.3 ± 7.2 (range: 73-100) postoperatively (P < 0.005). VAS scores declined from 4.2 ± 0.9 (range: 3-5.5) preoperatively to 0.5 ± 0.3 (range: 0-2) postoperatively (P < 0.001). On the weight bearing lateral view of the foot, Tomeno-Méary angle (TM lat) changed from −11.2 ± 4.2 (range: −17.2 to -2.8) preoperatively to -2.4 ± 3.9 (range: −10.2 to 5.2) degrees postoperatively (P < 0.001). Conclusions Fusion of talus-navicular joint and adjacent affected joint provide good clinical outcomes. CT/MRI scans are helpful to identify the adjacent joint arthritis and provide indications for individual treatment for Stage IV MWD.